Was Copernicus an Astrologer? From the Perspective of a Historian of Astrology - Sylwia Konarska-Zimnicka (Studia Historiae Scientiarum)
Nicolaus Copernicus’s achievements in the field of astronomy are widely known and undisputed, but few people know that he also studied astrology – in his time recognised as a science and a subject of academic lectures. Evidence of this activity, though scarce, is preserved in the margins of one of the popular astrological treatises of the 15th and 16th centuries, which was owned by Nicolaus Copernicus. Thanks to these marginal notes it is possible to undertake a consideration of the scale and reasons for the involvement of the astronomer in the exploration of astrology.